Assyrian Language and Writing in Ancient Iraq _ unpublished Building Bricks model - SALLEH, MAZNAH; M.ABDULKAREEM, QUSAY (Human Sustainability Procedia, 2018)
The Assyrian writing language on bricks which we intend to deal with isknown as “Launching Blocks“in the castles and temples building, and which have the form of Stamps or inscriptions(1)similar to the writing found onthe socketsofthe doors related to differentkings and rulers of different regions or cities in Mesopotamia. This type of cuneiform writing is documented as memorablesymbols to refer to building and to distinguish its type according to itslaunchor rebuilding(2). In order to observe such works, stonesand blocks were used as essential material